A New Mathematical Model for the Restoration Problem in Balanced Radial Distribution Systems - Romero, Ruben [UNESP]; Franco, John F. [UNESP]; Leao, Fabio B. [UNESP]; Rider, Marcos J. [UNESP]; De Souza, Eliane S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents a comprehensive mathematical model to solve the restoration problem in balanced radial distribution systems. The restoration problem, originally modeled as mixed integer nonlinear programming, is transformed into a mixed integer second-order cone programming problem, which can be solved efficiently using several commercial solvers based on the efficient optimization technique family branch and bound. The proposed mathematical model considers several objectives in a single objective function, using parameters to preserve the hierarchy of the different objectives: 1) maximizing the satisfaction of the demand, 2) minimizing the number of switch operations, 3) prioritizing the automatic switch operation rather than a manual one, and 4) prioritizing especial loads. General and specialized tests were carried out on a 53-node test system, and the results were compared with other previously proposed algorithms. Results show that the mathematical model is robust, efficient, flexible, and presents excellent performance in finding optimal solutions.
Keywords: Distribution system optimization; mixed integer second-order cone programming; restoration problem